Collaborative consumption and economic development: An analysis from the perspective of combating the coronavirus pandemic (covid-19) - Fraga, Fellipe Vilas Bôas; De Oliveira, Bruno Bastos; Rossignoli, Marisa [UNESP] (My University, 2020)
Objective: This article aims to examine socioeconomic development in times of a pandemic and to present the use of collaborative consumption as a way of promoting the social value of work and the search for full employment in view of the global spread of the coronavirus (COVID-19). Methodology: The work used the hypothetical-deductive method through bibliographic research and data analysis tools Results: It is concluded that, although humanity lives an era in which social chaos travels at the speed of globalization, as globalizing as the pandemic can be solidarity in difficult times, through various forms of market organization, such as the implementation of public policies and the use of collaborative consumption with respect to the social value of work and human development Contributions: The contribution of the present study was to consider national legislative measures to face the state of public calamity and support labor relations, as well as the importance of the social value of work for human development in times of pandemic, analyzing the relations focused on collaborative consumption with local commerce as a means to mitigate the crisis in labor relations in times of social withdrawal and recommendations for minimum mobility and commuting.
Consumo colaborativo e desenvolvimento econômico: Uma análise na perspectiva do combate à pandemia do coronavírus (covid-19)
Keywords: Collaborative consumption; Coronavirus; Full employment; Human development; Social Value of Work